Multilingual Content Management System using Drupal – A Case Study - Kumar Ray, Aswini; Ramesh, D. B. (Journal of Information and Knowledge, 2017)
This paper emphasizes the importance of having a true multilingual website and examines key issues in the process of constructing a successful multilingual site. This paper also explains a detailed strategy for creating a successful multilingual site and how a Content Management System (CMS) plays a significant role in creating multilingual websites. Presents stepby- step instructions for building a multilingual CMS for the S.O.A. University Library website using Drupal 7.39, an open source CMS. Also explains about the core modules and contributed modules of Drupal for implementation of multilingual features.